Interferon-Induced Transmembrane Protein 3 Expression Upregulation Is Involved in Progression of Hepatocellular Carcinoma. (17th March 2021) - Hou, Yuli; Wang, Shanshan; Gao, Mengdan; Chang, Jing; Sun, Jianping; Qin, Ling; Li, Ang; Lv, Fudong; Lou, Jinli; Zhang, Yonghong; Zhao, Yan
Abstract : Purpose . Interferon-induced transmembrane protein 3 (IFITM3) is a key signaling molecule regulating cell growth in some tumors, but its function and mechanism in hepatocellular carcinoma (HCC) remain unknown. Our study investigated the relationship between the expression of IFITM3 and HCC development. Material and Methods . IFITM3 expression was identified via multiple gene expression databases and investigated in HCC tissue samples. Then, PLC/PRF/5 cells were transfected with lentivirus to knock down and overexpress the expression of IFITM3. IFITM3 expression, cell proliferation, and migration were detected by qRT-PCR, western blotting, QuantiGene Plex 2.0 assay, immunohistochemistry, CCK-8, and wound healing tests. RNA-seq technology identified the PI3K/AKT/mTOR pathway as an IFITM3-related signaling pathway for investigation. Results . IFITM3 expression was higher in HCC tissues than in adjacent normal tissues, and the level of IFITM3 was higher in HCC tissues with low differentiation and metastatic potential than in those with high/medium differentiation and without metastatic potential. A higher RNA level of IFITM3 was found in samples with IFITM3 rs12252-CC genotype rather than the TT genotype. Knockdown of IFITM3 in PLC/PRF/5 cells inhibited cell proliferation and migration, blocked the expression of the PI3K/AKT/mTOR signaling pathway, and decreased the expression of vimentin. The results were opposite with the overexpression of IFITM3. Conclusion . Upregulation of IFITM3 plays a role in the development of HCC. Possibly through regulating HCC cell proliferation and migration, these effects are associated with the PI3K/AKT/mTOR signaling pathway. Upregulation of IFITM3 is also associated with the IFITM3 rs12252-CC genotype.